Report of the Working Group on Mineral Exploration and Development (Other than Coal and Lignite) for the Tenth Five Year Plan Fiscal Measures, Infrastructure Development and Environment Vol-IV - Planning Commission (Planning Commission, 2001)
Commensurate with economic liberalisation, the Government of India have taken series of new initiatives under the overall framework of the National Mineral Policy, 1993 (NMP) for growth of mineral sector. To give effect to the new National Mineral Policy, the Mines & Minerals (Regulation & Development) Act, 1957 (MMRD) was amended in 1994 and in December, 1999 renamed it as MMDR Act i.e. Mines & Minerals (Development & Regulation) Act. The changes in Act & Rules were incorporated with necessary guidelines to attract private investments both domestic and foreign.
Government of India, Planning Commission